2009
DOI: 10.1007/s00477-009-0317-z
|View full text |Cite
|
Sign up to set email alerts
|

Space–time forecasting using soft geostatistics: a case study in forecasting municipal water demand for Phoenix, Arizona

Abstract: Managing environmental and social systems in the face of uncertainty requires the best possible forecasts of future conditions. We use space-time variability in historical data and projections of future population density to improve forecasting of residential water demand in the City of Phoenix, Arizona. Our future water estimates are derived using the first and second order statistical moments between a dependent variable, water use, and an independent variable, population density. The independent variable is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…The mean trend model is “separable” because each of the smoothed components relies on either a purely spatial or purely temporal metric. The SSTM has performed well in numerous smaller-scale (i.e., state- or citywide) geostatistical studies (Christakos and Serre 2000; Lee et al 2010, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…The mean trend model is “separable” because each of the smoothed components relies on either a purely spatial or purely temporal metric. The SSTM has performed well in numerous smaller-scale (i.e., state- or citywide) geostatistical studies (Christakos and Serre 2000; Lee et al 2010, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Differences in neighborhood characteristics have been shown to influence water consumption patterns, perhaps by capturing (unobserved) effects of localized climate conditions, neighborhood socioeconomic and cultural differences, and variations in the provision of water infrastructure and maintenance. Several studies have conducted spatial analysis of water use at the census block group level (Breyer, Chang, & Parandvash, 2012;Chang et al, 2010;House-Peters et al, 2010;Lee, Chang, & Gober, 2015) and at the census tract scale (Balling et al, 2008;Guhathakurta & Gober, 2007;Lee, Wentz, & Gober, 2009;Wentz & Gober, 2007). Chang et al (2010) found that spatial regression and geographically weighted regression (GWR) may be better suited to account for variability in water usage across an urban area than typical ordinary least squares (OLS) models.…”
Section: Determinants Of Water Consumptionmentioning
confidence: 99%
“…Geospatial analyses have demonstrated how soft data that captures uncertainties can be used with Bayesian Maximum Entropy (BME) to improve downscaling of neighborhood-level water demand data [59,60]. In part by integrating error projections, BME methods were shown to be up to 44% more accurate than other methods (e.g., traditional kriging) that do not estimate such uncertainty [61]. Urban heat island data were also improved by extrapolating missing data, with the BME methods proving to be up to 13%-35% more accurate than traditional approaches [59].…”
Section: Inevitable Uncertainties In Decision-makingmentioning
confidence: 99%
“…Urban heat island data were also improved by extrapolating missing data, with the BME methods proving to be up to 13%-35% more accurate than traditional approaches [59]. Another technique-called the space-time interpolation environment (STIE)-was developed to analyze rich spatial and temporal datasets (e.g., from aerial imagery and weather stations) [61,62]. This process involves spatial and temporal interpolation, since both contextual factors are key.…”
Section: Inevitable Uncertainties In Decision-makingmentioning
confidence: 99%